2018
DOI: 10.1007/s11682-018-9914-0
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal dynamics of functional connectivity density in children with benign epilepsy with centrotemporal spikes

Abstract: Converging evidence has shown the link between benign epilepsy with centrotemporal spikes (BECTS) and abnormal functional connectivity among distant brain regions. However, prior research in BECTS has not examined the dynamic changes in functional connectivity as networks form. We combined functional connectivity density (FCD) mapping and sliding windows correlation analyses, to fully capture the functional dynamics in patients with respect to the presence of interictal epileptic discharges (IEDs). Resting-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 44 publications
2
34
0
1
Order By: Relevance
“…Network hubs facilitate efficient functional integration of information processing both within and between particular neural systems (Avena‐Koenigsberger, Misic, & Sporns, ). Subsequent FCD studies confirmed its sensitivity in detecting abnormalities of the functional connectivity hubs in psychiatric and neurological diseases (Lee et al, ; Li et al, ; Tomasi & Volkow, ).…”
Section: Introductionmentioning
confidence: 89%
“…Network hubs facilitate efficient functional integration of information processing both within and between particular neural systems (Avena‐Koenigsberger, Misic, & Sporns, ). Subsequent FCD studies confirmed its sensitivity in detecting abnormalities of the functional connectivity hubs in psychiatric and neurological diseases (Lee et al, ; Li et al, ; Tomasi & Volkow, ).…”
Section: Introductionmentioning
confidence: 89%
“…The sliding window method was applied to evaluate the dALFF for each participant using the DynamicBC toolbox (Liao et al, ). Previous studies proposed that the window length is an open but essential parameter in sliding‐window‐based resting‐state dynamics computation (Li et al, ; Li, Duan, et al, ; Liao et al, ) To avoid the introduction of spurious fluctuations, the minimum window length should be larger than 1/ f min , where f min is the minimum frequency of time series (Leonardi & Van De Ville, ; Li, Wang, et al, ). Here, a window length of 50 TR was considered as the optimal parameter to maintain the balance between capturing a rapidly shifting dynamic relationship and obtaining reliable estimates of the correlations between regions (Li, Liao, et al, ; Li, Wang, et al, ; Pang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In children with CECTS, increased variability in the precuneus, a core component of the DMN, appears to be associated with an earlier age of seizure onset . A positive correlation between the segregation of DMN components, that is, the extent to which the anatomic network components were able to function independently, and intelligence quotient (IQ), verbal comprehension, and perceptual reasoning has been reported .…”
Section: Functional Network In Cectsmentioning
confidence: 99%
“…19 In children with CECTS, increased variability in the precuneus, a core component of the DMN, appears to be associated with an earlier age of seizure onset. 20 A positive correlation between the segregation of DMN components, that is, the extent to which the anatomic network components were able to function independently, and intelligence quotient (IQ), verbal comprehension, and perceptual reasoning has been reported. 21 In other studies, however, tests of correlation between connectivity measures and IQ reveal no significant results even when performance in one or more domains is decreased in the children with CECTS.…”
Section: Default Mode Networkmentioning
confidence: 99%
See 1 more Smart Citation